Acute Ischemic Stroke After Moderate to Severe Traumatic Brain Injury: Incidence and Impact on Outcome. Issue 7 (July 2017) - Kowalski, Robert G.; Haarbauer-Krupa, Juliet K.; Bell, Jeneita M.; Corrigan, John D.; Hammond, Flora M.; Torbey, Michel T.; Hofmann, Melissa C.; Dams-O'Connor, Kristen; Miller, A. Cate; Whiteneck, Gale G.
Abstract : Background and Purpose—: Traumatic brain injury (TBI) leads to nearly 300 000 annual US hospitalizations and increased lifetime risk of acute ischemic stroke (AIS). Occurrence of AIS immediately after TBI has not been well characterized. We evaluated AIS acutely after TBI and its impact on outcome. Methods—: A prospective database of moderate to severe TBI survivors, admitted to inpatient rehabilitation at 22 Traumatic Brain Injury Model Systems centers and their referring acute-care hospitals, was analyzed. Outcome measures were AIS incidence, duration of posttraumatic amnesia, Functional Independence Measure, and Disability Rating Scale, at rehabilitation discharge. Results—: Between October 1, 2007, and March 31, 2015, 6488 patients with TBI were enrolled in the Traumatic Brain Injury Model Systems National Database. One hundred and fifty-nine (2.5%) patients had a concurrent AIS, and among these, median age was 40 years. AIS was associated with intracranial mass effect and carotid or vertebral artery dissection. High-velocity events more commonly caused TBI with dissection. AIS predicted poorer outcome by all measures, accounting for a 13.3-point reduction in Functional Independence Measure total score (95% confidence interval, −16.8 to −9.7; P <0.001), a 1.9-point increase in Disability Rating Scale (95% confidence interval, 1.3–2.5; P <0.001), and an 18.3-day increase in posttraumatic amnesia duration (95% confidence interval, 13.1–23.4; P <0.001). Conclusions—: Ischemic stroke is observed acutely in 2.5% of moderate to severe TBI survivors and predicts worse functional and cognitive outcome. Half of TBI patients with AIS were aged ⩽40 years, and AIS patients more often had cervical dissection. Vigilance for AIS is warranted acutely after TBI, particularly after high-velocity events. Abstract : Supplemental Digital Content is available in the text.